Feasibility studies and dynamics of catalytic liquid phase esterification reactions in a micro plant - Kulkarni, A. A.; Zeyer, K. -P.; Jacobs, T.; Kaspereit, M.; Kienle, Achim (Chemical Engineering Journal, 2008)
We present a new micro reactor concept which is suitable for investigations of heterogeneously catalyzed liquid phase reactions. In the set-up two reactants are mixed in a commercially available interdigital micro mixer. The outlet of the micro mixer is connected to a modular micro reactor that consists of stacked plates. Each plate contains a milled meandering channel filled with catalyst beads. By using a variable number of plates the residence time can be manipulated and thus adjusted for a specific task. The synthesis of butyl acetate is considered as a model reaction since it has been investigated in detail in conventional reaction systems. In a first step, some experimental results of the heterogeneously catalyzed reaction are presented. In the second part, the set-up is operated as a chromatographic reactor. Dynamic behaviour is investigated applying the frontal analysis mode and the elution chromatography mode. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: chromatographic reactor; heterogeneous catalysis; integrated process; modular micro reactor

Evaluation of multipoint dosing strategy in a miniaturized tubular reactor: nitration of salicylic acid - Debnath, Soujoy; Kienle, Achim; Kulkarni, Amol A. (Chemical Engineering & Technology, 2014)
A 2D non-isothermal reaction engineering model for a tubular reactor was developed for a complex reaction network of salicylic acid nitration. The influence of different operating and design parameters was studied to minimize the amount of secondary nitration products and limit the maximum temperature inside the reactor. Critical temperature effects were observed for larger reaction tubes, whereas close to isothermal conditions were perceived in smaller tubes. With single-point dosing of both reactants, complete conversion can be achieved but formation of secondary nitration products cannot be avoided. For a given number of dosing points, a suitable combination of the operating parameters allowed to achieve complete conversion and better yield of the desired product.
Keywords: Multipoint injection; nitration; Plug-flow reactor; Salicylic acid; Tubular reactor